A profile of U.S. home internet users and online shoppers : implications for retailers and e-tailers / Sandra McKay, Uday Tate and Mary Blalock - McKay, Sandra; Tate, Uday; Blalock, Mary (Faculty of Business and Management ; UiTM Press, 2002)
Both worldwide and within the U.S., Internet access increased dramatically between 1998 and 1999 and is projected to continue to rise at alarming rates. Currently, U.S. households with home Internet access are more likely to be white, located in urban areas, and have higher income and educational levels than those without home access. However, the Internet population is becoming more mainstream. Last year, women, seniors, and people with moderate incomes and educational levels increasingly came online. Online shopping exploded in 1999, posting end-of-year total sales of $20.2 billion. Implications of these emerging trends for retailers and e-tailers are examined in the paper.